Chemical constituents from aerial parts of Polyalthia Evecta (Pierre) Finet & Gagnep. Var. Attopeuensis - Sirinapa Nantapap (2018)
The first phytochemical investigation from aerial parts of Polyalthia evecta (Pierre) Finet & Gagnep. var. attopeuensis led to the isolation of six compounds, including two triterpenoids; stigmasterol (1) and β-sitosterol (2), two aporphine alkaloids; oxostephanine (3) and dicentrinone (4), one diureide of glyoxylic acid; allantoin (5) and one styryl lactone; goniothalamin (6). Characterization of all compounds was carried out by extensive spectroscopic analysis and comparison with literature. All compounds were previously isolated from Polyalthia, excepting dicentrinone (4) and goniothalamin (6) that are being reported for the first time from this genus.